AvgStudent
Full Member
- Joined
- Jan 1, 2022
- Messages
- 256
Hi, I was tasked with proving that addition is associative, assuming the Peano Axioms and followings are true: Can someone check if the proof is valid?
Given:
[imath]S:\N\to\N[/imath], [imath]s(n)=n+1[/imath], where [imath]s(n)[/imath] is the successor function.
Proof by induction:
Let [imath]S=\{l,m,n \in \N|(l+m)=n = l+(m+n)\}[/imath]
Base case:
[imath](l+m)+1=s(l+m)=l+s(m)=l+(m+1)\implies1\in S[/imath]
Induction:
[math](l+m)+(n+1)=(l+m)+s(n)\\ =s((l+m)+n)\\ =s(l+(m+n))\\ =l+s(m+n)\\ =l+(m+s(n))\\ =l+(m+(n+1))\\ \implies n+1 \in S [/math]Therefore, addition is associative for all [imath]n \in\N \quad \blacksquare[/imath]
Given:
[imath]S:\N\to\N[/imath], [imath]s(n)=n+1[/imath], where [imath]s(n)[/imath] is the successor function.
- [imath]s(n)=n+1[/imath]
- [imath]m+s(n)=s(m+n)[/imath]
Proof by induction:
Let [imath]S=\{l,m,n \in \N|(l+m)=n = l+(m+n)\}[/imath]
Base case:
[imath](l+m)+1=s(l+m)=l+s(m)=l+(m+1)\implies1\in S[/imath]
Induction:
[math](l+m)+(n+1)=(l+m)+s(n)\\ =s((l+m)+n)\\ =s(l+(m+n))\\ =l+s(m+n)\\ =l+(m+s(n))\\ =l+(m+(n+1))\\ \implies n+1 \in S [/math]Therefore, addition is associative for all [imath]n \in\N \quad \blacksquare[/imath]
Last edited: